Mirtazapine added to SSRIs or SNRIs for treatment resistant depression in primary care: phase III randomised placebo controlled trial (MIR). (31st October 2018) - Kessler, David S; MacNeill, Stephanie J; Tallon, Deborah; Lewis, Glyn; Peters, Tim J; Hollingworth, William; Round, Jeff; Burns, Alison; Chew-Graham, Carolyn A; Anderson, Ian M; Shepherd, Tom; Campbell, John; et al.
Abstract: Objective: To investigate the effectiveness of combining mirtazapine with serotonin-noradrenaline reuptake inhibitor (SNRI) or selective serotonin reuptake inhibitor (SSRI) antidepressants for treatment resistant depression in primary care. Design: Two parallel group multicentre phase III randomised placebo controlled trial. Setting: 106 general practices in four UK sites; Bristol, Exeter, Hull, and Keele/North Staffs, August 2013 to October 2015. Participants: 480 adults aged 18 or more years who scored 14 or more on the Beck depression inventory, second revision, fulfilled ICD-10 (international classification of diseases, 10th revision) criteria for depression, and had used an SSRI or SNRI for at least six weeks but were still depressed. 241 were randomised to mirtazapine and 239 to placebo, both given in addition to usual SSRI or SNRI treatment. Participants were stratified by centre and minimised by baseline Beck depression inventory score, sex, and current psychological therapy. They were followed up at 12, 24, and 52 weeks. 431 (89.8%) were included in the (primary) 12 week follow-up. Main outcome measures: Depressive symptoms at 12 weeks after randomisation, measured using the Beck depression inventory II score as a continuous variable. Secondary outcomes included measures of anxiety, quality of life, and adverse effects at 12, 24, and 52 weeks. Results: Beck depression inventory II scores at 12 weeks were lower in the mirtazapine group after adjustment for baseline scores and minimisation or stratification variables, although the confidence interval included the null (mean (SD) scores at 12 weeks: 18.0 (12.3) in the mirtazapine group, 19.7 (12.4) in the placebo group; adjusted difference between means −1.83 (95% confidence interval −3.92 to 0.27); P=0.09). Adverse effects were more common in the mirtazapine group and were associated with the participants stopping the trial drug. Conclusion: This study did not find evidence of a clinically important benefit for mirtazapine in addition to an SSRI or SNRI over placebo in a treatment resistant group of primary care patients with depression. This remains an area of important unmet need where evidence of effective treatment options is limited. Trial registration: Current Controlled Trials ISRCTN06653773 .